Manufacturing-Driven Insights into Structure, Mechanics, and Permeability of Asymmetric LSCF Membranes via Freeze Casting and Tape Casting - Valdir Pereira Junior; Priscila Lemes; Murilo Daniel de Mello Innocentini; Mara Gabriela Novy Quadri; Dachamir Hotza; Sergio Yesid Gómez González (Open Ceramics)
The performance of dense membranes is influenced by both material properties and design features, with thinner membranes exhibiting faster transport rates than thicker ones. However, mechanical limitations restrict the use of standalone thin membranes. A hierarchical structure approach is proposed to address this issue, consisting of a thin, dense layer supported by a porous substrate that provides mechanical strength. The porous support is engineered through microstructuring the pore architecture to enhance strength and permeation rates, as it governs overall oxygen transport in asymmetric membranes. This study combines freeze casting and tape casting to fabricate asymmetric LSCF membranes. The porous supports were manufactured using freeze casting, studying the effects of the freezing method, solids load, and binder concentration systematically evaluated through experimental design. The interaction between these variables and their impact on mechanical properties, porosity, and permeability was thoroughly analyzed. The freezing method significantly altered pore directionality, connectivity, stress strength, fracture strain, and permeability. While standalone dense membranes exhibited low mechanical strength, the porous support demonstrated up to 13-fold mechanical strength. The dense, thin membrane, produced by tape casting, was successfully coupled with the porous support, with no cracking or delamination observed at the interface after deposition and co-sintering.